Focus on the classical and non-classical functions of EZH2: Guide the development of inhibitors and degraders. (April 2022) - Zhang, Qiangsheng; Yang, Hongling; Feng, Qiang; Cao, Jiaying; Zhang, Yiqian; Li, Lu; Yu, Luoting
Abstract: Enhancer of zeste homologue 2 (EZH2, also known as KMT6A) is found to be a member of the histone lysine methyltransferase family. An increasing number of studies have shown that in addition to methylating histones, EZH2 plays a vital role in a variety of ways. The methylated substrates of EZH2 also include GATA4, AR/AR-related proteins, STAT3, Talin protein, and RORα. Meanwhile, EZH2 has been reported to form complexes with some proteins to perform other important biological functions as well as methylation. These complexes include: the EZH2-RelA-RelB complex, EZH2-ER-β-catenin complex, and β-catenin-PAF-EZH2-Mediator complex. Herein, we focus on the classical and non-classical functions of EZH2, and summarize anti-EZH2 therapeutic strategies. Finally, we highlight that understanding the physiological and pathological functions of EZH2 in specific indications can help the development of inhibitors or degraders. Graphical Abstract: ga1